Macroeconomics at the service of public policy - Sargent, Thomas J.; Vilmunen, Jouko (Oxford : Oxford University Press, 2013)
This book uses state of the art models from the frontier of macroeconomics to answer key questions about how the economy functions and how policy should be conducted. It includes contributions on the market as a bearer of risk, the European Debt crisis, and possible stagflation of the US economy.
Includes bibliographical references and index.
oif 16/06/15
Loan
Keywords: Macroeconomics; Economic policy